A Case Report of Compassion Focused Therapy (CFT) for a Japanese Patient with Recurrent Depressive Disorder: The Importance of Layered Processes in CFT - Kenichi Asano; Eiji Shimizu (Case Reports in Psychiatry)
Major depressive disorder is a common mental health problem around the world. To treat depression, cognitive behavioural therapy is highly recommended by some guidelines. However, there are reports pointing out the existence of patients who do not respond to cognitive behavioural therapy because of dissociation between thoughts and experiences. To treat such patients, compassion focused therapy was developed, but there are no reports of compassion focused therapy for Japanese patients. This report presents a case of compassion focused therapy for a Japanese female with major depressive disorder and suicidal feelings. After receiving compassion focused therapy, the patient recovered and began to have social interaction with others again. This case suggested the importance of psychoeducation, exercises involving compassionate images and breathing, and a compassionate relationship in conducting compassion focused therapy.